How does agricultural insurance affect income inequality within farmers? Based on survey data from Shandong Province, China - Zongyun She; Le Sun; Yanmei Yuan; Shengwei Chen (PLoS ONE, 2025)
To solidly promote common prosperity, the most arduous and heavy task still lies in rural areas. Agricultural insurance, as an important tool for supporting and benefiting agriculture, is of great significance in narrowing the income gap among farmers and achieving common prosperity in rural areas. This article uses survey data from 632 households in Shandong Province to empirically test the impact and mechanism of agricultural insurance on income inequality among farmers. It has been found that purchasing agricultural insurance can alleviate income inequality within farmers. This impact is achieved through three pathways: promoting the transfer of agricultural land, easing credit constraints, and optimizing labor resource allocation. Further research has found that purchasing agricultural insurance can significantly suppress income inequality among households in the dependency and stable periods, while having no impact on households in other stages of their life cycle. To promote common prosperity, this article believes that we should continue to promote the “expansion” of agricultural insurance, strengthen the coordination and cooperation between agricultural insurance and other agricultural support policies, and promote the differentiation of agricultural insurance products.